2018
DOI: 10.17851/1983-3652.11.3.228-251
|View full text |Cite
|
Sign up to set email alerts
|

Concepções de aprendizagem de línguas e o Duolingo: uma análise crítica sobre sua proposta e experiências de aprendizes

Abstract: RESUMO: O Duolingo é o aplicativo mais baixado no mundo por aprendizes que procuram uma ferramenta digital gratuita e com design atrativo para aprendizagem de línguas. O presente trabalho investiga a concepção de aprendizagem de usuários desse aplicativo e suas propostas, buscando responder à seguinte questão de pesquisa: como aprendizes que usam ou já usaram o aplicativo Duolingo definem suas experiências com aprendizagem de línguas e com as ofertas do aplicativo? A metodologia desta pesquisa é de base qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The game-like features of Duolingo, such as gaining streaks, have been found to boost students' motivation [54], potentially contributing to improved performance among the participants in this study. Furthermore, students' perception of the application's ease of use aligns with previous research findings in the field [55]. Duolingo is claimed to keep users engaged and more motivated, which is supported by a considerable amount of research [56,57].…”
Section: Duolingosupporting
confidence: 74%
See 1 more Smart Citation
“…The game-like features of Duolingo, such as gaining streaks, have been found to boost students' motivation [54], potentially contributing to improved performance among the participants in this study. Furthermore, students' perception of the application's ease of use aligns with previous research findings in the field [55]. Duolingo is claimed to keep users engaged and more motivated, which is supported by a considerable amount of research [56,57].…”
Section: Duolingosupporting
confidence: 74%
“…Loewen and colleagues [18] (2019) identified a relationship between utilizing Duolingo for learning a language and enhanced results on a comprehensive examination evaluating listening, speaking, writing, reading and lexico-grammatical proficiency. Users of Duolingo reported a notably high level of contentment derived from the application's utilization [55,58]. Several studies highlighted participants' positive perceptions of Duolingo as a beneficial tool [59].…”
Section: Duolingomentioning
confidence: 99%
“…Moreover, the game-like features of Duolingo such as gaining streaks may increase students' motivation (Huynh et al, 2018) and this may have helped the students in this study to increase their performance. Besides, students' finding the application easy to use is also aligned with the studies in the field (Marques-Schafer & da Silva Orlando, 2018). Furthermore, it is seen that students who experienced Duolingo as part of their English classes found it beneficial suggesting positive outcomes of the intervention.…”
Section: Discussionmentioning
confidence: 55%
“…In other words, Duolingo is limited by its method of language teaching and the range of techniques it uses to deliver instruction (Shulman, 1986). Some learners in Marques‐Schafer and da Silva Orlando's (2018) study reported wanting more explicit grammatical feedback. In other words, there are also limitations to the way in which Duolingo represents content to learners to facilitate learning (Shulman, 1986).…”
Section: Can Artificial Intelligence Replace Language Teachers?mentioning
confidence: 97%